Numerical Investigation of Heat Transfer, Fluid Flow and Formation of Emissions in Diesel Engines - Firat, Mujdat (Amer Soc Mechanical Engineers, 2014)
The present study has been performed on heat transfer, fluid flow and formation of emissions in a diesel engine by different engine parameters. The analysis aims at an investigation of flow field, heat transfer, combustion pressure and formation of emission by means of numerical simulation which is using as parameter; hole number of injector and crank angle. Numerical simulations are performed using the AVL-FIRE commercial software depending on the crank angle. This software is successfully used in internal combustion engine applications, and its validity has been accepted. In this paper, k-zeta-f is preferred as turbulence model and SIMPLE/PISO used as algorithms. Thus, results are presented with pressure traces, temperature curves and NOx and soot levels for engine operating conditions. In addition, the relationship between the spray behaviors and combustion characteristics including NOx emissions, soot emissions, combustion pressure and temperature were illustrated through this analysis.
ASME International Mechanical Engineering Congress and Exposition (IMECE2013) -- NOV 15-21, 2013 -- San Diego, CA